Pemanfaatan Bottom Ash Batubara Menjadi Silika Gel Sebagai Absorben Pb+ pada Limbah Industri Minuman di Bayuasin - Nurjanah, Rizki; Zamhari, Mustain; Yerizam, Muhammad (Innovative: Journal Of Social Science Research, 2024)
Improving the quality of life and welfare through industrial development in various sectors often results in negative impacts such as production waste. One type of waste produced from coal combustion is fly ash and bottom ash, both of which were categorized as hazardous waste (B3) according to government regulations before 2021. With regulatory changes in 2021, this waste can be utilized more flexibly after obtaining Environmental Approval. This study examines the use of bottom ash as an adsorbent to reduce heavy metals in industrial wastewater. Bottom ash from PT PUSRI Palembang was processed into silica gel using the sol-gel method and NaOH activation, with the liquid waste used coming from the liquid waste of the beverage industry in Banyuasin. The results showed that silica gel successfully made from bottom ash has an adsorption capacity following the Langmuir model, with a value of 1.743 mg/g and an adsorption efficiency of 73.69%. The optimal NaOH concentration was found at a 3 M ratio with an average efficiency of 70.84%.